Strategi Digital Marketing Pada Media Sosial Dalam Meningkatkan Kunjungan Pasien RSOMH Bukittinggi - Doris Septeria; Helmi Ali (CV. ITTC INDONESIA, 2025)
This study aims to design a digital marketing strategy on social media at the DR. Drs. M. Hatta Brain Hospital in Bukittinggi. Current problems indicate that the social media of the DR. Drs. M. Hatta Brain Hospital in Bukittinggi has not been fully optimized as a means to disseminate information about health services and conduct health promotions to the wider community, does not yet have a framework in digital marketing, and has never been analyzed social media activities, especially Instagram. The main focus of this study is to identify a digital marketing development framework based on the five stages of the maturity model, analyze social media activities, and develop a digital strategy that suits the needs of the institution. The method used is a qualitative approach, where data collection is carried out through field observations, distributing questionnaires, and in-depth interviews with hospital leaders and other relevant informants. The analysis is carried out systematically by identifying the hospital's digital marketing position in each stage of maturity, evaluating the strengths and weaknesses of social media strategies through a SWOT analysis, and designing a concrete development strategy. The results of this study produced a digital marketing maturity model design that reflects the readiness and direction of digital development of DR. Drs. M. Hatta Brain Hospital in Bukittinggi Hospital, and presents an applicable strategy in strengthening the hospital's digital presence, expanding the reach of hospital information services and digital-based health information.